Essays on fintech adoption, cashless payments, and cashless sales: evidence from Saudi Arabia - Alatram, Khaled Abdulrahman Saleh (2025)
Financial technology (Fintech) is reshaping global financial systems, offering opportunities for financial inclusion, economic growth, and cost reduction. Saudi Arabia presents a unique context for studying Fintech adoption due to its state-led financial transformation under Vision 2030. This thesis adopts an inductive (theory-building) approach to investigate the determinants of Fintech adoption, digital payment behaviours, and cashless transactions through three interconnected essays. The first essay examines the determinants of individual Fintech adoption, focusing on socio-demographic and financial factors. Using a survey of 1,666 respondents, the study finds that gender, age, employment status, and financial literacy significantly influence adoption. Younger, more educated individuals exhibit higher adoption rates, while financial well-being and inclusion emerge as key enablers of digital financial participation. The findings highlight the need for targeted financial literacy programs and consumer protection mechanisms. The second essay analyses digital payment behaviours using a dataset of 716 million transactions over 36 months. It differentiates between payment channels, including Chip-and-PIN, contactless, digital wallet, and E-commerce, revealing variations across demographic groups. Results show that females and expatriates conduct lower-value transactions, while unemployed individuals and younger users engage in higher-value digital payments. These findings challenge conventional assumptions and underscore the influence of demographic and socio-economic characteristics on financial behaviours. The third essay investigates macroeconomic and structural determinants of cashless sales and cash withdrawals using 30.42 billion cashless transactions and 28.30 billion cash withdrawals over 25 years. The study assesses the impact of the COVID-19 pandemic, geopolitical risks, temperature variations, and cultural events such as Ramadan. It finds that the pandemic negatively impacted cashless sales in Saudi Arabia, contrasting with global trends. Geopolitical risks had limited sectoral or urban impacts, while infrastructure, particularly international airports and seaports, significantly enhanced urban cashless transactions. This thesis advances understanding of Fintech adoption and cashless financial behaviours in Saudi Arabia, contributing to Financial Inclusion Theory, Behavioural Finance, and the Technology Acceptance Model (TAM). It provides transaction-level insights and informs regulatory strategies to promote financial inclusion, offering valuable lessons for policymakers and financial institutions in emerging economies.